The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Obituary Gerhart Drews - Georg Fuchs; Rolf Thauer (Archives of Microbiology, 2023)

Ecosystem transpiration and evaporation: Insights from three water flux partitioning methods across FLUXNET sites - Jacob A. Nelson; Oscar Pérez‐Priego; Sha Zhou; Rafael Poyatos; Yao Zhang; Peter D. Blanken; Teresa E. Gimeno; Georg Wohlfahrt; Ankur R. Desai; Beniamino Gioli; Jean‐Marc Limousin; Damien Bonal; et al. (Global Change Biology, 2020)
We apply and compare three widely applicable methods for estimating ecosystem transpiration ( T ) from eddy covariance (EC) data across 251 FLUXNET sites globally. All three methods are based on the coupled water and carbon relationship, but they differ in assumptions and parameterizations. Intercomparison of the three daily T estimates shows high correlation among methods ( R between .89 and .94), but a spread in magnitudes of T /ET (evapotranspiration) from 45% to 77%. When compared at six sites with concurrent EC and sap flow measurements, all three EC‐based T estimates show higher correlation to sap flow‐based T than EC‐based ET. The partitioning methods show expected tendencies of T /ET increasing with dryness (vapor pressure deficit and days since rain) and with leaf area index (LAI). Analysis of 140 sites with high‐quality estimates for at least two continuous years shows that T /ET variability was 1.6 times higher across sites than across years. Spatial variability of T /ET was primarily driven by vegetation and soil characteristics (e.g., crop or grass designation, minimum annual LAI, soil coarse fragment volume) rather than climatic variables such as mean/standard deviation of temperature or precipitation. Overall, T and T /ET patterns are plausible and qualitatively consistent among the different water flux partitioning methods implying a significant advance made for estimating and understanding T globally, while the magnitudes remain uncertain. Our results represent the first extensive EC data‐based estimates of ecosystem T permitting a data‐driven perspective on the role of plants’ water use for global water and carbon cycling in a changing climate.

Journal Club - Volkmar Braun; Georg Fuchs; Michael Schloter; Torsten Schubert; Jochen Graw; Daniela Kruck; Johannes Sander; Gerhart Drews; Stefan Schild; Klaus Hantke; Sandra Wiegand; Alexander Westermann; et al. (BIOspektrum, 2020)

The AlpArray Seismic Network: A Large-Scale European Experiment to Image the Alpine Orogen - György Hetényi; Irene Molinari; John Clinton; Götz Bokelmann; István Bondár; Wayne C. Crawford; Jean-Xavier Dessa; Cécile Doubre; Wolfgang Friederich; Florian Fuchs; Domenico Giardini; Zoltán Gráczer; et al. (Surveys in Geophysics, 2018)

An Interactive Approach for Exploration of Flows Through Direction-Based Filtering - Katerina Vrotsou; Georg Fuchs; Natalia Andrienko; Gennady Andrienko (Journal of Geovisualization and Spatial Analysis, 2017)

The Arnon–Buchanan cycle: a retrospective, 1966–2016 - Bob B. Buchanan; Reidun Sirevåg; Georg Fuchs; Ruslan N. Ivanovsky; Yasuo Igarashi; Masaharu Ishii; F. Robert Tabita; Ivan A. Berg (Photosynthesis Research, 2017)

Vom Anorganischen zum Organischen - Georg Fuchs (BIOspektrum, 2011)

Anaerobic metabolism of phenol in proteobacteria and further studies of phenylphosphate carboxylase - Sirko Schmeling; Georg Fuchs (Archives of Microbiology, 2009)

Abundance, distribution, and territory areas of rock-dwelling Lake Tanganyika cichlid fish species - Christian Sturmbauer; Corinna Fuchs; Georg Harb; Elisabeth Damm; Nina Duftner; Michaela Maderbacher; Martin Koch; Stephan Koblmüller (Hydrobiologia, 2008)

Landscape controls of CH 4 fluxes in a catchment of the forest tundra ecotone in northern Siberia - HEINER FLESSA; ANDREJ RODIONOV; GEORG GUGGENBERGER; HANS FUCHS; PAUL MAGDON; OLGA SHIBISTOVA; GALINA ZRAZHEVSKAYA; NATALIA MIKHEYEVA; OLEG A. KASANSKY; CHRISTIAN BLODAU (Global Change Biology, 2008)
Terrestrial ecosystems in northern high latitudes exchange large amounts of methane (CH 4 ) with the atmosphere. Climate warming could have a great impact on CH 4 exchange, in particular in regions where degradation of permafrost is induced. In order to improve the understanding of the present and future methane dynamics in permafrost regions, we studied CH 4 fluxes of typical landscape structures in a small catchment in the forest tundra ecotone in northern Siberia. Gas fluxes were measured using a closed‐chamber technique from August to November 2003 and from August 2006 to July 2007 on tree‐covered mineral soils with and without permafrost, on a frozen bog plateau, and on a thermokarst pond. For areal integration of the CH 4 fluxes, we combined field observations and classification of functional landscape structures based on a high‐resolution Quickbird satellite image. All mineral soils were net sinks of atmospheric CH 4 . The magnitude of annual CH 4 uptake was higher for soils without permafrost (1.19 kg CH 4 ha −1 yr −1 ) than for soils with permafrost (0.37 kg CH 4 ha −1 yr −1 ). In well‐drained soils, significant CH 4 uptake occurred even after the onset of ground frost. Bog plateaux, which stored large amounts of frozen organic carbon, were also a net sink of atmospheric CH 4 (0.38 kg CH 4 ha −1 yr −1 ). Thermokarst ponds, which developed from permafrost collapse in bog plateaux, were hot spots of CH 4 emission (approximately 200 kg CH 4 ha −1 yr −1 ). Despite the low area coverage of thermokarst ponds (only 2.1% of the total catchment area), emissions from these sites resulted in a mean catchment CH 4 emission of 3.8 kg CH 4 ha −1 yr −1 . Export of dissolved CH 4 with stream water was insignificant. The results suggest that mineral soils and bog plateaux in this region will respond differently to increasing temperatures and associated permafrost degradation. Net uptake of atmospheric CH 4 in mineral soils is expected to gradually increase with increasing active layer depth and soil drainage. Changes in bog plateaux will probably be much more rapid and drastic. Permafrost collapse in frozen bog plateaux would result in high CH 4 emissions that act as positive feedback to climate warming.

Phenylacetate Metabolism in Thermophiles: Characterization of Phenylacetate-CoA Ligase, the Initial Enzyme of the Hybrid Pathway in Thermus thermophilus - Tobias J. Erb; Wael Ismail; Georg Fuchs (Current Microbiology, 2008)

Storage and mobility of black carbon in permafrost soils of the forest tundra ecotone in Northern Siberia - GEORG GUGGENBERGER; ANDREJ RODIONOV; OLGA SHIBISTOVA; MATTHIAS GRABE; OLEG A. KASANSKY; HANS FUCHS; NATALIA MIKHEYEVA; GALINA ZRAZHEVSKAYA; HEINER FLESSA (Global Change Biology, 2008)
Boreal permafrost soils store large amounts of organic carbon (OC). Parts of this carbon (C) might be black carbon (BC) generated during vegetation fires. Rising temperature and permafrost degradation is expected to have different consequences for OC and BC, because BC is considered to be a refractory subfraction of soil organic matter. To get some insight into stocks, variability, and characteristics of BC in permafrost soils, we estimated the benzene polycarboxylic acid (BPCA) method‐specific composition and storage of BC, i.e. BPCA‐BC, in a 0.44 km 2 ‐sized catchment at the forest tundra ecotone in northern Siberia. Furthermore, we assessed the BPCA‐BC export with the stream draining the catchment. The catchment is composed of various landscape units with south‐southwest (SSW) exposed mineral soils characterized by thick active layer or lacking permafrost, north‐northeast (NNE) faced mineral soils with thin active layer, and permafrost‐affected raised bogs in plateau positions showing in part thermokarst formation. There were indications of vegetation fires at all landscape units. BC was ubiquitous in the catchment soils and BPCA‐BC amounted to 0.6–3.0% of OC. This corresponded to a BC storage of 22–3440 g m −2 . The relative contribution of BPCA‐BC to OC, as well as the absolute stocks of BPCA‐BC were largest in the intact bogs with a shallow active layer followed by mineral soils of the NNE aspects. In both landscape units, a large proportion of BPCA‐BC was stored within the permafrost. In contrast, mineral soils with thick active layer or lacking permafrost and organic soils subjected to thermokarst formation stored less BPCA‐BC. Permafrost is, hence, not only a crucial factor in the storage of OC but also of BC. In the stream water BPCA‐BC amounted on an average to 3.9% of OC, and a yearly export of 0.10 g BPCA‐BC m −2 was calculated, most of it occurring during the period of snow melt with dominance of surface flow. This suggests that BC mobility in dissolved and colloidal phase is an important pathway of BC export from the catchment. Such a transport mechanism may explain the high BC concentrations found in sediments of the Arctic Ocean.

Autotrophic CO2 fixation pathways in archaea (Crenarchaeota) - Michael Hügler; Harald Huber; Karl Otto Stetter; Georg Fuchs (Archives of Microbiology, 2003)

A new purple sulfur bacterium isolated from a littoral microbial mat, Thiorhodococcus drewsii sp. nov. - Annette Zaar; Georg Fuchs; Jochen R. Golecki; Jörg Overmann (Archives of Microbiology, 2003)

Aerobic metabolism of phenylacetic acids in Azoarcus evansii - Magdy Mohamed; Wael Ismail; Johann Heider; Georg Fuchs (Archives of Microbiology, 2002)

Phylogenetic and metabolic diversity of bacteria degrading aromatic compounds under denitrifying conditions, and description of Thauera phenylacetica sp. nov., Thauera aminoaromatica sp. nov., and Azoarcus buckelii sp. nov. - Tahar Mechichi; Erko Stackebrandt; Nasser Gad'on; Georg Fuchs (Archives of Microbiology, 2002)

Differential induction of enzymes involved in anaerobic metabolism of aromatic compounds in the denitrifying bacterium Thauera aromatica - J. Heider; Matthias Boll; Klaus Breese; Sabine Breinig; Christa Ebenau-Jehle; Ulrich Feil; Nasser Gad'on; Diana Laempe; Birgitta Leuthner; M. El-Said Mohamed; Sabine Schneider; Gerhard Burchhardt; et al. (Archives of Microbiology, 1998)

Anaerobic metabolism of 2-hydroxybenzoic acid (salicylic acid) by a denitrifying bacterium - C. F. C. Bonting; Georg Fuchs (Archives of Microbiology, 1996)

Anaerobic degradation of m -cresol via methyl oxidation to 3-hydroxybenzoate by a denitrifying bacterium - C. F. C. Bonting; Sabine Schneider; Gü nther Schmidtberg; Georg Fuchs (Archives of Microbiology, 1995)

Anaerobic degradation ofm-cresol via methyl oxidation to 3-hydroxybenzoate by a denitrifying bacterium - Cornelus F. C. Bonting; Sabine Schneider; Günther Schmidtberg; Georg Fuchs (Archives of Microbiology, 1995)

Purification and properties of benzyl alcohol dehydrogenase from a denitrifying Thauera sp. - Thomas Biegert; Uwe Altenschmidt; Christoph Eckerskorn; Georg Fuchs (Archives of Microbiology, 1995)

Anaerobic oxidation of toluene (analogues) to benzoate (analogues) by whole cells and by cell extracts of a denitrifying Thauera sp. - Thomas Biegert; Georg Fuchs (Archives of Microbiology, 1995)

Genotoxic risk for humans due to work place exposure to ethylene oxide: remarkable individual differences in susceptibility - Jürgen Fuchs; Ute Wullenweber; Jan Georg Hengstler; Heinz Günter Bienfait; Gerd Hiltl; Franz Oesch (Archives of Toxicology, 1994)

Evidence that phenol phosphorylation to phenylphosphate is the first step in anaerobic phenol metabolism in a denitrifying - Achim Lack; Georg Fuchs (Archives of Microbiology, 1994)

Evidence that phenol phosphorylation to phenylphosphate is the first step in anaerobic phenol metabolism in a denitrifying Pseudomonas sp. - Achim Lack; Georg Fuchs (Archives of Microbiology, 1994)

Enzymes of the reductive citric acid cycle in the autotrophic eubacterium Aquifex pyrophilus and in the archaebacterium Thermoproteus neutrophilus - Monika Beh; Gerhard Strauss; Robert Huber; Karl-Otto Stetter; Georg Fuchs (Archives of Microbiology, 1993)

Anaerobic oxidation of phenylacetate and 4-hydroxyphenylacetate to benzoyl-coenzyme A and CO2 in denitrifying Pseudomonas sp. - Magdy El-Said Mohamed; Birgit Seyfried; Andreas Tschech; Georg Fuchs (Archives of Microbiology, 1993)

Purification and characterization of phenylacetate-coenzyme A ligase from a denitrifying Pseudomonas sp., an enzyme involved in the anaerobic degradation of phenylacetate - Magdy El-Said Mohamed; Georg Fuchs (Archives of Microbiology, 1993)

Purification of glutaryl-CoA dehydrogenase from Pseudomonas sp., an enzyme involved in the anaerobic degradation of benzoate - Ulrich Hrtel; Elke Eckel; Jrgen Koch; Georg Fuchs; Dietmar Linder; Wolfgang Buckel (Archives of Microbiology, 1993)

Anaerobic degradation of toluene in denitrifying Pseudomonas sp.: indication for toluene methylhydroxylation and benzoyl-CoA as central aromatic intermediate - Uwe Altenschmidt; Georg Fuchs (Archives of Microbiology, 1991)

Differential expression of enzyme activities initiating anoxic metabolism of various aromatic compounds via benzoyl-CoA - Werner Dangel; Ruth Brackmann; Achim Lack; Magdy Mohamed; Jrgen Koch; Brigitte Oswald; Birgit Seyfried; Andreas Tschech; Georg Fuchs (Archives of Microbiology, 1991)

Anaerobic degradation of phenylacetate and 4-hydroxyphenylacetate by denitrifying bacteria - Birgit Seyfried; Andreas Tschech; Georg Fuchs (Archives of Microbiology, 1991)

Anaerobic degradation of cresols by denitrifying bacteria - Angelika Rudolphi; Andreas Tschech; Georg Fuchs (Archives of Microbiology, 1991)

Anaerobic metabolism of resorcyclic acids (m-dihydroxybenzoic acids) and resorcinol (1,3-benzenediol) in a fermenting and in a denitrifying bacterium - Claudia Kluge; Andreas Tschech; Georg Fuchs (Archives of Microbiology, 1990)

NADP+-specific 2-oxoglutarate dehydrogenase in denitrifying Pseudomonas species - Christa Lochmeyer; Georg Fuchs (Archives of Microbiology, 1990)

Anaerobic degradation of phenol via carboxylation to 4-hydroxybenzoate: in vitro study of isotope exchange between 14CO2 and 4-hydroxybenzoate - Andreas Tschech; Georg Fuchs (Archives of Microbiology, 1989)

Activation of aromatic acids and aerobic 2-aminobenzoate metabolism in a denitrifying Pseudomonas strain - Klaus Ziegler; Reiner Buder; Jochen Winter; Georg Fuchs (Archives of Microbiology, 1989)

Oxidative and reductive acetyl CoA/carbon monoxide dehydrogenase pathway in Desulfobacterium autotrophicum - Rolf Schauder; Andrea Preu; Mike Jetten; Georg Fuchs (Archives of Microbiology, 1988)

Oxidative and reductive acetyl CoA/carbon monoxide dehydrogenase pathway in Desulfobacterium autotrophicum - Siegfried Lnge; Rudolf Scholtz; Georg Fuchs (Archives of Microbiology, 1988)

Anaerobic metabolism of cyclohexanol by denitrifying bacteria - Werner Dangel; Andreas Tschech; Georg Fuchs (Archives of Microbiology, 1988)

Acetate oxidation to CO2 in anaerobic bacteria via a novel pathway not involving reactions of the citric acid cycle - Rolf Schauder; Bernhard Eikmanns; Rudolf K. Thauer; Fritz Widdel; Georg Fuchs (Archives of Microbiology, 1986)

Detection of acetyl coenzyme A as an early CO2 assimilation intermediate in Methanobacterium - Marion Rhlemann; Klaus Ziegler; Erhard Stupperich; Georg Fuchs (Archives of Microbiology, 1985)

Autotrophic synthesis of activated acetic acid from two CO2 in Methanobacterium thermoautotrophicum - Ute Holder; Dumbravita-Ella Schmidt; Erhard Stupperich; Georg Fuchs (Archives of Microbiology, 1985)

Autotrophic synthesis of activated acetic acid from two CO2 inMethanobacterium thermoautotrophicum - Erhard Stupperich; Georg Fuchs (Archives of Microbiology, 1984)

Autotrophic synthesis of activated acetic acid from two CO2 inMethanobacterium thermoautotrophicum - Erhard Stupperich; Georg Fuchs (Archives of Microbiology, 1984)

Carbon assimilation pathways in sulfate reducing bacteria. Formate, carbon dioxide, carbon monoxide, and acetate assimilation by Desulfovibrio baarsii - Kathrin Jansen; Rudolf K. Thauer; Fritz Widdel; Georg Fuchs (Archives of Microbiology, 1984)

Autotrophic CO2 fixation in Acetobacterium woodii - Gerolf Eden; Georg Fuchs (Archives of Microbiology, 1983)

Total synthesis of acetyl coenzyme a involved in autotrophic CO2 fixation inAcetobacterium woodii - Gerolf Eden; Georg Fuchs (Archives of Microbiology, 1982)

Carbohydrate synthesis from acetyl CoA in the autotroph Methanobacterium thermoautotrophicum - Kathrin Jansen; Erhard Stupperich; Georg Fuchs (Archives of Microbiology, 1982)

Phosphoenolpyruvate synthetase inMethanobacterium thermoautotrophicum - Jaime Eyzaguirre; Kathrin Jansen; Georg Fuchs (Archives of Microbiology, 1982)

Products of CO2 fixation and 14C labelling pattern of alanine in Methanobacterium thermoautotrophicum pulse-labelled with 14CO2 - Erhard Stupperich; Georg Fuchs (Archives of Microbiology, 1981)

Acetate thiokinase and the assimilation of acetate in Methanobacterium thermoautotrophicum - Gerhard Oberlies; Georg Fuchs; Rudolf K. Thauer (Archives of Microbiology, 1980)

Autotrophic CO2 fixation in Chlorobium limicola. Evidence for the operation of a reductive tricarboxylic acid cycle in growing cells - Georg Fuchs; Erhard Stupperich; Gerolf Eden (Archives of Microbiology, 1980)

Autotrophic CO2 fixation in Chlorobium limicola. Evidence against the operation of the Calvin cycle in growing cells - Georg Fuchs; Erhard Stupperich; Rolf Jaenchen (Archives of Microbiology, 1980)

Acetyl CoA, a central intermediate of autotrophic CO2 fixation in Methanobacterium thermoautotrophicum - Georg Fuchs; Erhard Stupperich (Archives of Microbiology, 1980)

Function of fumarate reductase in methanogenic bacteria (Methanobacterium) - Georg Fuchs; Erhard Stupperich; Rudolf K. Thauer (Archives of Microbiology, 1978)

Acetate assimilation and the synthesis of alanine, aspartate and glutamate inMethanobacterium thermoautotrophicum - Georg Fuchs; Erhard Stupperich; Rudolf K. Thauer (Archives of Microbiology, 1978)

Evidence for an incomplete reductive carboxylic acid cycle in Methanobacterium thermoautotrophicum - Georg Fuchs; Erhard Stupperich (Archives of Microbiology, 1978)